Genetic variation within the coat color gene of Melanocortin 1 Receptor (MC1R) in Mong Cai pigs of Vietnam - CAO THI THU THUY; CHU DUC HA; TRAN DUC LONG; TONG VAN HAI; TRAN THI CHI; TA THI HONG QUYEN; VU HAI YEN; NGO THI MINH KHANH; NGUYEN QUOC TRUNG; NGO THANH TRUNG (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Thuy CTT, Ha CD, Long TD, Hai TV, Long ST, Chi TT, Quyen TTH, Yen VH, Khanh NTM, Trung NQ, Trung NT. 2023. Genetic variation within the coat color gene of Melanocortin 1Receptor (MC1R) in Mong Cai pigs of Vietnam. Biodiversitas 24: 1735-1741. Pig (Sus scrofa) is considered one of the major domesticated animals in Vietnam. Various indigenous pig varieties have been successfully developed as the Vietnamese's main daily meat source. However, little information has been reported about the conservation of these indigenous pig varieties. In this study,the Mong Cai, a prized domestic pig breed in Vietnam, is well-characterized by a black saddle on the hips extending to the lower abdomen. As a result of the introduction of exotic breeds and crossbreeding, Mong Cai pigs exhibited various phenotypic characteristics and coat colors. We constructed a database of Melanocortin 1Receptor(MC1R) coding sequences, including the MC1Rsequences of 26 Mong Cai and 20 other pig breeds from Europe and Asia. Subsequently, 12 haplotypes were determined using 18 mutations in 46 individuals. The phylogenetic tree result indicated that the Mong Cai population was distributed into two distinct haplotypes. Moreover, Mong Cai pigs could belong to the Asian clade; however, six Mong Cai individuals formed a distinct cluster. These six individuals carried the nt729G gene, which is prevalent in European pigs. In addition, our study could provide a solid foundation for further investigation of the evolution of indigenous pig varieties in Vietnam.